Environmental dynamics: unraveling the nexus of air pollution, population agglomeration, and sustainable economic development in China: a provincial-level empirical analysis - Yan, Jun; Liu, Chang; Xiao, Bo; Wang, Suzhen (Frontiers in Environmental Science, 2024)
Sustainable economic development is a hot issue in current research, and it is of great significance to analyze the impacts of air pollution and population concentration on sustainable economic development. Based on literature review and theoretical research, this study finds that air pollution and population agglomeration have significant impacts on economic sustainability. By analyzing the data on economic sustainability, SO2 emissions, population agglomeration, urbanization level, industrial structure, living standards of residents and the level of use of foreign capital in China from 2011-2021 and constructing an individual single-factor fixed-effects model, we find that SO2 emissions are negatively correlated with economic sustainability, and that the direction and intensity of their impacts are affected by the level of urbanization, industrial structure, living standards of residents, and other factors. The influence of population agglomeration on economic sustainable development shows a positive correlation. At the same time, we further confirm that the impact of the above influencing factors on sustainable economic development varies from region to region through subregional studies.. Therefore, in order to promote sustainable economic development, it is necessary to further identify the stage of sustainable economic development according to the actual situation of different regions, and to effectively integrate factors including the environment, population, urbanization, industrial structure, etc..